2021
DOI: 10.1111/os.12985
|View full text |Cite
|
Sign up to set email alerts
|

Improved Perioperative Sleep Quality or Quantity Reduces Pain after Total Hip or Knee Arthroplasty: A Systematic Review and Meta‐Analysis

Abstract: Objective: To investigate the effects of improved perioperative sleep on pain, analgesic consumption, and postoperative nausea and vomiting (PONV) in patients who were undergoing total knee arthroplasty (TKA) or total hip arthroplasty (THA).Methods: Original studies published from 1 January 1970 to 30 September 2020 were queried in three unique databases using a common search term. The searches sought randomized controlled trials (RCT) investigating the effectiveness of sleep quality or quantity interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…However, in a meta-analysis of 416 patients with total hip or knee arthroplasty, the authors found that increased DST did not improve PONV. This is not consistent with our results because we focused on the severity of PONV, whereas the previous study focused more on its incidence ( 45 ). Second, we found that reduced DST could aggravate anxiety and depression during the perioperative period.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in a meta-analysis of 416 patients with total hip or knee arthroplasty, the authors found that increased DST did not improve PONV. This is not consistent with our results because we focused on the severity of PONV, whereas the previous study focused more on its incidence ( 45 ). Second, we found that reduced DST could aggravate anxiety and depression during the perioperative period.…”
Section: Discussioncontrasting
confidence: 99%
“…Traumatic arthritis is the most common complication after acetabular fracture. Through the analysis of 569 patients with acetabular fractures, some scholars reported that the overall incidence of postoperative traumatic arthritis was 17%, of which the incidence of complete reduction was 10% and that of incomplete reduction was 35% [ 6 ]. Many literatures have pointed out that the postoperative effect is not satisfactory, which is often accompanied by joint dislocation, marginal compression, and ipsilateral femoral head fracture such as in the initial operation, which failed to fix the fracture, the necessary bone graft treatment, and often bring about serious complications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] A recent systematic review identified that improved preoperative sleep reduced pain levels and analgesic consumption after TKR. 23 Guidance from the National Institute for Health and Care Excellence (NICE) and European Alliance of Associations for Rheumatology advises avoidance of pharmacological therapy for long-term management of sleep issues and recommends behavioural approaches as firstline treatment. 24 25 Non-pharmacological sleep interventions are potentially more sustainable and cost-effective, with lower risk of side effects.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Previous trials on sleep and joint replacement have predominantly focused on perioperative and postoperative pharmacological interventions 20–22. A recent systematic review identified that improved preoperative sleep reduced pain levels and analgesic consumption after TKR 23. Guidance from the National Institute for Health and Care Excellence (NICE) and European Alliance of Associations for Rheumatology advises avoidance of pharmacological therapy for long-term management of sleep issues and recommends behavioural approaches as first-line treatment 24 25.…”
Section: Introductionmentioning
confidence: 99%